The legal framework of the Islamic financial system: a study on the cases in Malaysia / Najahudin Lateh … [et al.] - Lateh, Najahudin; Mohamed Adil, Mohamed Azam; Md Rejab, Siti Noorbiah; Sahri, Mardhiyyah (Universiti Teknologi MARA Cawangan Selangor, 2010)
The legal framework of the Islamic financial system in Malaysia is subjected to civil law. This is because the Federal Constitution which divides the jurisdiction of the civil and shari’ah matters is silent on whether the Shari’ah Court has the power to hear cases or disputes relating to Islamic finance. As such, numerous interpretations of the Civil Court in contractual and financial applications are given. Some of them conflict with the Shari’ah law and rather emphasise on the usage of the civil law. Henceforth, this study will be focusing on the results and interpretations of the Civil Court in cases of Islamic finance and banking. Furthermore, the authors recommend some amendments to the Constitution and relevant Acts, to strengthen the laws relating to Islamic finance and to enhance the role of the Shari’ah Court.